شعرية السرد في المجموعة القصصية (دائرة الحلم والعواصف) لجميلة زنير - دقعة, قدور جبار, حنان سميرة (University of El-oued, 2021)
تهدف هذه الدراسة إلى البحث عن شعرية السرد في المجموعة القصصية (دائرة الحلم والعواصف) لجميلة زنير، حيث وقع اختيارنا على هذه المدونة نظراً لنُدرة الدراسات حولها وكذلك للانتشار الواسع لفن القصة القصيرة. يقوم هذا البحث على المنهج البنيوي الذي يساعد في تقسيمات بنية القصة القصيرة والبحث في أغوار بنية النص، و المنهج الأسلوبي للبحث في الجانب المجازي من استعارة وكناية وتشبيه، والمنهج السيميائي للوصول إلى الدلالات الكامنة في النص خاصة على مستوى العنوان، مستعينين في ذلك بآلية الوصف والتحليل. ولبلوغ ذلك، استند البحث على خطة تضمنت مدخلاً وفصلين: مدخل يبحث في مفاهيم حول الشعرية والقصة القصيرة، تناولنا فيه ملامح الشعرية في التراث العربي والنقد الغربي وكذلك النقد العربي المعاصر. ثم تناولنا مفاهيم حول القصة القصيرة عامة والقصة القصيرة في الجزائر خاصة من حيث النشأة والتطور، دون أن ننسى القصة القصيرة النسوية. وتناولنا في الفصل الأول دلالة العنوان وشعرية اللغة التي وظفتها الكاتبة ، كما تطرقنا لمفاهيم الشخصية مع تحليل لبنيتها في مدونة البحث، أما الفصل الثاني قدمنا فيه شعرية البنية الزمنية من خلال توظيف تقنيات المفارقات والمدة، وشعرية البنية المكانية مستعينين بالتقاطبات المكانية (ثنائية المغلق والمفتوح). توصل البحث إلى ضبط مجموعة من النتائج المهمة أكدت على تمكن الكاتبة جميلة زنير من توظيف شعرية السرد في مجموعتها القصصية، والوصف النفسي للشخصيات وكذلك التوظيف الجمالي للزمان والمكان بفنية عالية. وفي الأخير نرجو أن تُسلّطَ الأضواء على أعمال الكاتبة جميلة زنير لما تحمله من خصائص سردية قوية تنفرد بها عن غيرها وخاصة مدونة بحثنا هذا، من أجل فتح آفاق جديدة له. This study aims at looking for the poetics of narration in the collection of «The Circle of Dream & Storms" written by Djamila Zenir. We have selected this corpus because of the lack of studies about it and the widespread of short stories art. This research is based on structural methods as it helps in short story structure divisions and in researching the depths of text structure. It is based also on the stylistic methods in searching the rhetorical part as metaphor, metonymy, and simile. It is founded too on the semiotic methods to achieve the connotations that reside in the text especially at the title level, using within all of that the descriptive and the analytical approach. To that end, the research was based on a plan that included one entry and two chapters: The first was looking for some concepts about poetics and short story. We discussed the features of poetics in the Arab heritage, the western critics, and the contemporary Arabic critique. Then we tackled concepts about short stories in general and that in Algeria, especially in terms of genesis and evolution, without forgetting the feminist short story. In the first chapter, we dealt with the title significance, the poetics of language used by the author, and the concepts of personality with the analysis of its structure in the research corpus. In the second chapter, we presented the poetics of temporal structure by using the mechanism of paradox and duration. We brought up also the poetics of spatial structure by using the spatial polarity (closed and open binary) The research has achieved a set of important findings that confirmed that Djamila Zenir mastered the use of the poetics of narration in her collection, the psychological description of figures, and the high aesthetic employment of time and space. At the end and for more perspectives, we hope that the lights will be shed on Djamila Zenir's works for its strong narrative properties unique for her especially our corpus.
Keywords: جميلة زنير، الشعرية، القصة القصيرة، دائرة الحلم والعواصف، السرد.; Djamila Zenir, Poetics, Short story, The Circle of Dream and Storm, the Narration